Characterization of hERG1 channel role in mouse colorectal carcinogenesis. (22nd July 2013) - Fiore, Antonella; Carraresi, Laura; Morabito, Angela; Polvani, Simone; Fortunato, Angelo; Lastraioli, Elena; Femia, Angelo P.; De Lorenzo, Emanuele; Caderni, Giovanna; Arcangeli, Annarosa
Abstract: The human ether‐à‐go‐go‐related gene (hERG)1 K + channel is upregulated in human colorectal cancer cells and primary samples. In this study, we examined the role of hERG1 in colorectal carcinogenesis using two mouse models: adenomatous polyposis coli (Apc min/+ ) and azoxymethane (AOM)‐treated mice. Colonic polyps of Apc min/+ mice overexpressed mERG1 and their formation was reverted by the hERG1 blocker E4031. AOM was applied to either hERG1‐transgenic (TG) mice, which overexpress hERG1 in the mucosa of the large intestine, or wild‐type mice. A significant increase of both mucin‐depleted foci and polyps in the colon of hERG1‐TG mice was detected. Both the intestine of TG mice and colonic polyps of Apc min/+ showed an upregulation of phospho‐Protein Kinase B (pAkt)/vascular endothelial growth factor (VEGF‐A) and an increased angiogenesis, which were reverted by treatment with E4031. On the whole, this article assigns a relevant role to hERG1 in the process of in vivo colorectal carcinogenesis. Abstract : We studied the role of hERG1 in colorectal carcinogenesis using Apc min/+ and azoxymethane (AOM)‐treated mice as models. In Apc min/+ mice, the development of colonic polyps, shown to overexpress hERG1, was reverted by hERG1 blockers. AOM triggered a higher number of preneoplastic lesions such as mucin‐depleted foci and polyps in the colon of transgenic mice, which overexpress hERG1, compared to wild‐type mice. In either model, a hERG1‐dependent increase of both VEGF‐A and angiogenesis was detected.